Effects of the built environment on physical activity: a systematic review of longitudinal studies taking sex/gender into account - Antonina Tcymbal; Yolanda Demetriou; Anne Kelso; Laura Wolbring; Kathrin Wunsch; Hagen Wäsche; Alexander Woll; Anne K. Reimers (Komiyama Printing Co. Ltd, 2020)
Abstract Background Individual health behavior is related to environmental and social structures. To promote physical activity (PA) effectively, it is necessary to consider structural influences. Previous research has shown the relevance of the built environment. However, sex/gender differences have yet not been considered. The aim of this systematic review was to identify built environmental determinants of PA by taking sex/gender into account. Methods A systematic literature search was carried out using six electronic databases (PubMed, CINAHL, SportDiscus, PsycInfo, Scopus, Web of Knowledge) to identify studies analyzing the effect of changes in the built environment on PA, taking sex/gender into account. To be included, studies had to be based on quantitative data and a longitudinal study design. Changes in the built environment had to be objectively assessed. The methodological quality of the studies was examined using the QualSyst tool for examining risk of bias. Results In total, 36 studies published since 2000 were included in this review. The data synthesis revealed that the majority of reviewed studies found the built environment to be a determinant of PA behavior for both, males and females, in a similar way. Creating a new infrastructure for walking, cycling, and public transportation showed a positive effect on PA behavior. Findings were most consistent for the availability of public transport, which was positively associated with overall PA and walking. The improvement of walking and cycling infrastructure had no effect on the overall level of PA, but it attracted more users and had a positive effect on active transportation. In women, the availability of public transport, safe cycling lanes, housing density, and the distance to daily destinations proved to be more relevant with regard to their PA behavior. In men, street network characteristics and road environment, such as intersection connectivity, local road density, and the presence of dead-end roads, were more important determinants of PA. Conclusion This review sheds light on the relevance of the built environment on PA. By focusing on sex/gender differences, a new aspect was addressed that should be further analyzed in future research and considered by urban planners and other practitioners.